THE IMPACT OF FINANCIAL SECRECY ON CORRUPTION - Matitaputty, Jean Stevany (E-Jurnal Akuntansi TSM, 2025)
Corruption poses a potential challenge to the economic growth and financial stability of a country. It is closely related to the regulation and legal system that governs various economic activities. This research aims to examine the influence of financial secrecy on corruption. Financial secrecy is supported by a country's legal system to conceal illegally obtained assets that can potentially cause corruption. The quantitative method with the panel data regression technique was used in this research. Financial secrecy was measured using the Financial Secrecy Index (FSI) and corruption was measured using the Corruption Perception Index (CPI). The total sample size was 302, originating from 118 countries worldwide, over three years (2018, 2020, and 2022). The results indicate that financial secrecy has a positive effect on corruption. Furthermore, this study provides more specific evidence through a robustness test, which shows that financial secrecy has a positive effect in developed countries and a negative effect in developing countries. Financial secrecy can be minimized if a country commits to information exchange to combat corruption, as applied by the G20 countries. This is supported by the result finding that financial secrecy has no effect on corruption in the G20 country category but has a positive effect in the non-G20 country category.